Increased CD95 (Fas) and PD‐1 expression in peripheral blood T lymphocytes in COVID‐19 patients. (18th August 2020) - Bellesi, Silvia; Metafuni, Elisabetta; Hohaus, Stefan; Maiolo, Elena; Marchionni, Federica; D'Innocenzo, Simone; La Sorda, Marilena; Ferraironi, Manuela; Ramundo, Francesco; Fantoni, Massimo; Murri, Rita; Cingolani, Antonella; et al.
Summary: A low count of CD4 + and CD8 + lymphocytes is a hallmark laboratory finding in the coronavirus disease 2019 (COVID‐19). Using flow cytometry, we observed significantly higher CD95 (Fas) and PD‐1 expression on both CD4 + T and CD8 + T cells in 42 COVID‐19 patients when compared to controls. Higher CD95 expression in CD4 + cells correlated with lower CD4 + counts. A higher expression of CD95 in CD4 + and CD8 + lymphocytes correlated with a lower percentage of naive events. Our results might suggest a shift to antigen‐activated T cells, expressing molecules increasing their propensity to apoptosis and exhaustion during COVID‐19 infection.